Energy and Economic Analysis of Life Cycle Zero Energy Building in the Temperate Region - Zhiyong Zhou (Tehnički Vjesnik, 2019)
Life cycle zero energy buildings (LCZEBs) can present energy use more accurately than net zero energy buildings (NZEBs). Economic benefits are crucial for residents to accept LCZEBs. However, few relevant case studies have been conducted. A comparative analysis between a NZEB and a LCZEB with a multi-story apartment in a temperate region that meets the requirements of local building energy codes as the reference building was conducted in this study to ascertain economic feasibility of LCZEB. First, a building model and an energy model were established on the basis of site test, survey, and monitoring data. Then, the energy balances of the NZEB and LCZEB were calculated on the basis of the results of energy simulation and the foregoing data. Finally, the LCZEB and NZEB were realized on the condition that high thermal performance materials and high energy efficiency building equipment were adopted in accordance with the principle of maximizing net present value (NPV) and solar energy was fully utilized. Results demonstrate that solar hot water and photovoltaic systems are critical to the NZEB and LCZEB. Annual net energy (ANE) and annual NPV per square meter of thermal collector are −571.11 kWh and $455.5, respectively, and ANE and annual NPV per square meter of photovoltaic panel are −115.62 kWh and $13.2. The NZEB and LCZEB are economically feasible in the temperate region although the NZEB is superior to the LCZEB in terms of economic benefits. Their NPVs for the calculation period (20 years) are $15369.64 and $4718.77, and their payback periods are 11 and 16 years. This study can provide references for energy and economic optimization of NZEBs and LCZEBs.